EFEK PEMBERIAN ORGANIK TITHONIA DAN PUPUK UREA TERHADAP RESPON PERTUMBUHAN BIBIT KELAPA SAWIT - Simon Haholongan, Sidabuke; Harahap, Fitra Syawal; Iman , Arman (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
Seedlings which look prima is a prerequisite for the success of oil palm cultivation. Besides, because of the factors in the pre-nursery genetic, the provision of nutrients in early growth seedlings has an important role performance determine the appearance of the seedlings thoroughly. This study aims to determine the influence of the growth of oil palm seedlings at each concentration of organic fertilizer tithonia and fertilizer of urea for pre-nursery. The experiment was carried out from Oktober 2023 to April 2024 in the Experimental Garden of the Faculty of Science and Technology, the University of Labuhanbatu Rantauprapat with a height of 13 meters above sea level. The experimental design used was a Randomized Block Design with a factorial pattern that is repeated three times. The experimental design used was a Randomized Block Design with a factorial pattern that is repeated three times. The first factor includes the dose of Organic Fertilizer Tithonia (ton/ha) comprising of three standards, namely T0 = 0 ton/ha, T1 = 10 ton/ha, T2 = 20 tons/ha and the second factor was fertilizer dosage Uera which consists of four levels, namely U0 = 0 kg/ha, U1 = 100 kg/ha, T2 = 200 kg/ha, U3 = 300 kg/ha. The experimental results show that there are significant interactions of organic fertilizer Tithonia with fertilizers urea on plant height (cm) and leaf area of oil palm seedlings (cm2). Treatment of organic fertilizer tithonia 20 tons/ha with fertilizer urea 300 kg/ha yield plant height and leaf area of oil palm seedlings the best for pre-nursery.